OPTIMAL INCOME TAXATION WITH QUASI-LINEAR PREFERENCES REVISITED - Robin Boadway; Katherine Cuff; Maurice Marchand (Queen's University, Department of Economics, 1999)
With quasi-linear in leisure preferences, closed-form solutions for the marginal tax rates and the marginal utility of consumption under utilitarian and maxi-min objectives depend only on the skill distribution. Bunching induced by binding second-order incentive conditions also depends only on the distribution, but does not affect solutions in the non-bunched range. These are affected if bunching is caused by binding non-negative income constraints. Specific skill distributions are considered and it shown that the pattern of marginal tax rates depend critically on whether or not the skill distribution is truncated at the upper end.
Keywords: H21; H23; 330; Optimal Income Tax; Quasi-Linear Preferences